2013
DOI: 10.4049/jimmunol.1301079
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Toxin Directly Enhances IL-17A Production from Human CD4+ T Cells

Abstract: The significance of Th17 cells and interleukin (IL)-17A signaling in host defense and disease development has been demonstrated in various infection and autoimmune models. In addition, the generation of Th17 cells is highly influenced by microbes. However, the specific bacterial components capable of shaping Th17 responses have not been well defined. The goals of this study are to understand how a bacterial toxin, cholera toxin (CT), modulates Th17-dominated response in isolated human CD4+ T cells, and what ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Since the cytokines and the receptors involved in the production of IL-17A and IFN-γ share common components, it is important to know if distinctive T cell subsets expressing these cytokines exist in ruminants as they appear to in other mammalian species. We found that the major T cell subsets (CD4+ve and WC-1+ve) can express IL-17A (Figures 5 and 6), consistent with reports in humans [50] and mice [51, 52]. We found CD8+ve IL-17A for cattle PBMC but had insufficient cells to confirm their presence in PMA/ionomycin-stimulated ovine PBMC.…”
Section: Discussionsupporting
confidence: 89%
“…Since the cytokines and the receptors involved in the production of IL-17A and IFN-γ share common components, it is important to know if distinctive T cell subsets expressing these cytokines exist in ruminants as they appear to in other mammalian species. We found that the major T cell subsets (CD4+ve and WC-1+ve) can express IL-17A (Figures 5 and 6), consistent with reports in humans [50] and mice [51, 52]. We found CD8+ve IL-17A for cattle PBMC but had insufficient cells to confirm their presence in PMA/ionomycin-stimulated ovine PBMC.…”
Section: Discussionsupporting
confidence: 89%
“…126128 Specifically, T H 1 cells are more sensitive than T H 2 cells to inhibition by CT. 129,130 However, in our study, CT upregulated IL-17A production by human CD4 + T cells and also promoted T H 17-cell differentiation. 131 The addition of cAMP analogs mimicked the CT effect on IL-17A induction, thus suggesting the involvement of cAMP-signaling pathway in the regulation of IL-17A production. Utilizing different cAMP analogs and the promoter-reporter activity assay, we demonstrated that CT-induced IL-17A production occurs via a cAMP-PKA pathway.…”
Section: Mechanisms Of Ct-induced Th17 Responsesmentioning
confidence: 88%
“…In addition, in vitro HIV infection also dampens the T cells’ proliferative ability through elevated intracellular cAMP levels . In contrast to its immune suppression, our group and others found that CT and cAMP also induces Th17 responses by acting on dendritic cells or T cells . In this study, we demonstrate that CT induces IL‐17A expression by the activation of a cAMP/PKA/CREB cascade, then CREB trans ‐activating IL‐17A promoter by binding to the cis ‐regulatory element, CRE motif at −183, of the promoter.…”
Section: Discussionmentioning
confidence: 56%
“…The constructs were termed IL17p/WT (wild‐type), IL17p/CREmt1, IL17p/CREmt2 and IL17p/CREmt1/2. Primers used to create the mutations were described previously . CREB1‐specific small interfering RNA (siRNA) non‐targeted oligomer controls were purchased from Life Technologies (Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation